Peripheral-specific Y1 receptor antagonism increases thermogenesis and protects against diet-induced obesity - Yan, Chenxu; Zeng, Tianshu; Lee, Kailun; Nobis, Max; Loh, Kim; Gou, Luoning; Xia, Zefeng; Gao, Zhongmin; Bensellam, Mohammed; Hughes, Will; Lau, Jackie; Zhang, Lei; et al. (Nature communications, 2021)
Obesity is caused by an imbalance between food intake and energy expenditure (EE). Here we identify a conserved pathway that links signalling through peripheral Y1 receptors (Y1R) to the control of EE. Selective antagonism of peripheral Y1R, via the non-brain penetrable antagonist BIBO3304, leads to a significant reduction in body weight gain due to enhanced EE thereby reducing fat mass. Specifically thermogenesis in brown adipose tissue (BAT) due to elevated UCP1 is enhanced accompanied by extensive browning of white adipose tissue both in mice and humans. Importantly, selective ablation of Y1R from adipocytes protects against diet-induced obesity. Furthermore, peripheral specific Y1R antagonism also improves glucose homeostasis mainly driven by dynamic changes in Akt activity in BAT. Together, these data suggest that selective peripheral only Y1R antagonism via BIBO3304, or a functional analogue, could be developed as a safer and more effective treatment option to mitigate diet-induced obesity. Neuropeptide Y signalling in the periphery contributes to the regulation of metabolic and energy homeostasis. Here the authors show that blocking Y1R signalling in peripheral tissues using the selective antagonist BIBO3304 ameliorates diet-induced obesity and improves whole-body glucose metabolism.